A Symmetric Model of Viscous Relaxing Fluid. An Evolution Problem - Zakora, D. (Журнал математической физики, анализа, геометрии, 2012)
An evolution problem on small motions of the viscous rotating relaxing fluid in a bounded domain is studied. The problem is reduced to the Cauchy problem for the first-order integro-differential equation in a Hilbert space. Using this equation, we prove a strong unique solvability theorem for the corresponding initial-boundary value problem.